A study of Chinese cross-border M&A integration - Song, Huimin (2019)
Chinese cross-border mergers and acquisitions (M&As), particularly post M&A integration, is still a relatively poorly understood phenomenon. The extant literature on the topic has attempted to examine the factors that can explain the integration outcome of Chinese companies’ cross-border M&As (CBMA). Indeed, some China-specific frameworks, or Chinese CBMA integration frameworks, have been proposed to better understand the phenomenon. These include the so-called light-touch integration framework and courtship-marriage-birth framework. These conceptualization of Chinese CBMA have provided some answers to questions related to integration outcome and have shown the role of both culture and strategy. While insightful, they still have certain lacunae. In particular, this extant Chinese literature of integration outcome is somewhat narrow (e.g., focus on ‘integration mode’), ignores strategic review as part of strategic factors, ignores cross-cultural psychology as part of cultural factors, and considers only one aspect of mediating factors (through intermediaries).